Comparison of Lead (Pb) Content Analysis Using Atomic Absorption Spectrophotometry with Wet and Dry Destruction Methods in Body Lotion Preparations in Semarang City - Muhammad Shidqi Naufal Athalla; Endah Widhihastuti (Journal of Science and Technology Research for Pharmacy, 2025)
Many body lotions are found in circulation without a BPOM RI registration number, which can raise concerns about lead metal contamination. The lead metal content in body lotion can be sourced from the raw material, namely water. Lead metal levels in water range from 0,011 mg/L to 0,076 mg/L. Determination of lead levels uses an Atomic Absorption Spectrophotometry instrument. The requirement for analysis using Atomic Absorption Spectrophotometry is that the sample must be in solution form, so a destruction process is necessary because the body lotion sample is in semi-solid form. This study aims to compare two commonly used destruction methods, namely wet and dry destruction. The methodology in this study consists of qualitative analysis, method validation, and quantitative analysis. The test results with qualitative analysis showed negative lead metal content. The results of the Atomic Absorption Spectrophotometry method validation were: linearity (R2) of 0,9999; LoD of 0,024 mg/L; LoQ of 0,080 mg/L; precision (%RSD) of 0,61%; accuracy (%Recovery) of 100,09% with quantitative results of the percentage of wet digestion sample content, results were: 1,2264 ± 2,96%; 1,7687 ± 4,24%; 1,5036 ± 3,75%; 1,1807 ± 2,92%; and 1,5606 ± 3,88%. This can happen because the wet destruction method is better to use than the dry destruction method which can be seen from the %Recovery.